2000
DOI: 10.1016/s0006-3495(00)76563-5
|View full text |Cite
|
Sign up to set email alerts
|

Solution Conformations of a Trimannoside from Nuclear Magnetic Resonance and Molecular Dynamics Simulations

Abstract: N-linked oligosaccharides often act as ligands for receptor proteins in a variety of cell recognition processes. Knowledge of the solution conformations, as well as protein-bound conformations, of these oligosaccharides is required to understand these important interactions. In this paper we present a model for the solution conformations sampled by a simple trimannoside, methyl 3, 6-di-O-(alpha-D-mannopyranosyl)-alpha-D-mannopyranoside, which contains two of the most commonly found glycosidic linkages in N-lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 63 publications
4
49
1
Order By: Relevance
“…6, panels C and D) 6 . The simulations predict a single and extremely broad free energy minimum centered on state XV and spanning ≈120° in both ϕ and ψ .…”
Section: Resultsmentioning
confidence: 92%
“…6, panels C and D) 6 . The simulations predict a single and extremely broad free energy minimum centered on state XV and spanning ≈120° in both ϕ and ψ .…”
Section: Resultsmentioning
confidence: 92%
“…Extensive conformational sampling is required to access the multiple conformers of N-glycans. For this reason, past conventional MD simulations in explicit solvent have been limited to small fragments like mono-, di-, or trisaccharides (Sayers and Prestegaud 2000;Kim et al 2009;Kirschner and Woods 2001;Almond 2005;Perić-Hassler et al 2010;Corzana et al 2004;Landström and Widmalm 2010), or larger fragments with short sampling (Naidoo et al 1997;Woods et al 1998;André et al 2009). …”
Section: Molecular Dynamics Simulations Of N-glycansmentioning
confidence: 99%
“…[8] Molecular dynamic simulations of trimannoside revealed high flexibility of the (1→6) linkage. [9] Later, molecular dynamic simulation studies of eight disaccharides (including gentiobiose) were carried out [10] and showed in particular that (1→6)-linked disaccharides were characteristic with an increased flexibility. Conformational analysis of (1→6) disaccharides usually consists of making Ramachandran-like maps, which depict potential energy dependence on three dihedral angles defined around the glycosidic linkage.…”
Section: Introductionmentioning
confidence: 99%
“…The preparation of such maps is a difficult task due to the "local minima problem." [9,13] At each grid point, the arrangement of all exocyclic groups should be taken into account, which requires 3 9 × 18 3 relaxed optimizations assuming that conformational space would be searched with a resolution of φ, ψ, and ω torsion angles at 20 • .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation